Promoting Physical Activity in Adapted Physical Education. Issue 4 (4th May 2018) - Yun, Joonkoo; Beamer, Jennifer
Abstract : The importance of physical activity has received considerable attention during the past decade. Physical education has been viewed as a cost-effective way to promote physical activity as a public health initiative. In fact, the Centers for Disease Control and Prevention recommends that a "substantial percentage" of students' overall physical activity should be obtained through school physical education. However, promoting physical activity as a part of adapted physical education (APE) has not been widely advocated within the current literature. The purpose of this article is to provide justification for physical activity promotion within the APE setting and to briefly address strategies for physical activity promotion. This article includes (1) federal legislation and regulations related to APE, (2) a discussion on the definition of physical activity, and (3) physical activity promotion strategies within and beyond APE classes.